Exploring the unknown territories in the new normal world of COVID - Sukhminder Jit Singh Bajwa; Ritu Gupta; Ajay Wahi; S. P. S. Goraya (Wolters Kluwer Medknow Publications, 2020)
It is now well known that the severe acute respiratory syndrome (SARS-CoV-2) originated in the Wuhan province of Hubei, China in 2019. Having spread across different countries of the world, this highly contagious disease has posed many challenges for the healthcare workers to work without endangering themselves and their patients' wellbeing. Several things are yet not clear about the virus and the presence or absence of the virus in the cerebrospinal fluid (CSF) is currently a debated topic. This article reports the perioperative management of two coronavirus disease-19 positive cases, one of whom was a pregnant patient. Their CSF samples, which were collected during the administration of spinal anesthesia, tested to be negative for viral reverse transcription polymerase chain reaction (RT-PCR) test. We wish to highlight from these cases, that during spinal anesthesia, CSF in mildly symptomatic COVID-19 cases probably does not pose a risk of transmission to the anesthesiologist. However, we suggest that due to the varied presentations of the virus, health care personnel, especially anesthesiologists have to be careful during the perioperative management of such cases.